2004
DOI: 10.1177/070674370404900209
|View full text |Cite
|
Sign up to set email alerts
|

Bupropion Sustained Release Treatment Reduces Fatigue in Cancer Patients

Abstract: Q uality of life (QOL) issues are particularly important for cancer patients. Fatigue, which is generally difficult to treat (1-3), seriously interferes with QOL by substantially diminishing patient ability to carry out meaningful daily activities (4). There is considerable diagnostic confusion over cancer-related fatigue (CRF) in the literature (5). Depending on the sample of patients and the type of measure used, prevalence estimates of fatigue during cancer treatment range from 25% to 99%. Between 17% and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(31 citation statements)
references
References 36 publications
0
28
0
3
Order By: Relevance
“…Most drugs were not compared with placebo or did not show significant benefit compared with placebo (Fig. 3) [7,8,[103][104][105][106][107][108][109][110][111][112][113][114][115][116][117][118]. One drug, methylphenidate, showed promising results [111][112][113]119], but in the latest and largest trials, no improvement of fatigue by this treatment was found compared with placebo [114,120,121].…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
“…Most drugs were not compared with placebo or did not show significant benefit compared with placebo (Fig. 3) [7,8,[103][104][105][106][107][108][109][110][111][112][113][114][115][116][117][118]. One drug, methylphenidate, showed promising results [111][112][113]119], but in the latest and largest trials, no improvement of fatigue by this treatment was found compared with placebo [114,120,121].…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
“…64 Bupropion has reduced fatigue in cancer patients and may lower tumor necrosis factor alpha but is a second-line agent in advanced disease because of seizure risk. 65,66 Tricyclics are effective for depression in cancer patients but are also second-line agents because of their frequent side effects (Table 2).…”
Section: Treatmentmentioning
confidence: 99%
“…Bupropion (Wellbutrin-SR ® ; GlaxoSmithKline, Philadelphia) is an atypical antidepressant, unrelated to tricyclic antidepressants or selective serotonin reuptake inhibitors, that has been used to treat chronic fatigue syndrome and fatigue associated with multiple sclerosis [62][63][64]. We identified two studies (6% of total) of bupropion sustained-release (SR) in the treatment of CRF [42,43]. In these open-label case series, bupropion SR (100-300 mg/day) was associated with improvements in fatigue scores within 2-4 weeks of the start of treatment.…”
Section: Antidepressantsmentioning
confidence: 99%